2019
DOI: 10.1002/cam4.2199
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive genomic profiling of small cell lung cancer in Chinese patients and the implications for therapeutic potential

Abstract: Background Small cell lung cancer (SCLC) is one of the deadliest malignancies and accounts for nearly 15% of lung cancers. Previous study had revealed the genomic characterization of SCLC in Western patients. However, little is known about that in Chinese SCLC patients. Methods Formalin‐fixed paraffin‐embedded tumor tissues and matched blood samples from 122 Chinese SCLC patients were collected for next generation sequencing to detect 450 cancer‐related genes. All patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 28 publications
1
24
1
Order By: Relevance
“…It was suggested in a previous study that Notch1 was highly expressed in Chinese patients with small cell LC 15. It was also pointed out that overexpression of Notch1 could promote the proliferation, invasion, and migration of NCI-H358 cells and H1299 cells 16,17.…”
Section: Resultsmentioning
confidence: 93%
“…It was suggested in a previous study that Notch1 was highly expressed in Chinese patients with small cell LC 15. It was also pointed out that overexpression of Notch1 could promote the proliferation, invasion, and migration of NCI-H358 cells and H1299 cells 16,17.…”
Section: Resultsmentioning
confidence: 93%
“…However, the most common genetic alterations include inactivation of the tumor suppressor genes TP53 and RB1 [16,17]. Hu et al demonstrated that the most frequently altered genes in small cell lung cancer were as followed: TP53 (93.4%), RB1 (78.7%), LRP1B(18.9%), KMT2D (15.6%), FAT1 (11.5%), KMT2C (11.5%),STK24 (11.5%), FAM135B (10.7%), and NOTCH1 (10.7%) [10]. The results were derived from genomic pro ling of 122 Chinese patients.…”
Section: Discussionmentioning
confidence: 99%
“…The genes were captured and sequenced with a mean depth of 800X, using Illumina NextSeq 500 (Illumina, Inc). Genomic alterations (GAs) were identi ed by the alignment of sequences from tissues and matched normal lung tissue, following the previously reported methods [10]. Tumor mutation burden (TMB) was estimated by counting the somatic mutations, containing SNVs and Indels, per megabase of the sequence examined on each patient.…”
Section: Next-generation Sequencingmentioning
confidence: 99%
“…Of them, two patients were detected with concurrent TP53 and RB1 mutations, which are typical molecular features of SCLC. 10 The remaining patient harbored concurrent TP53 p.Arg342* and PIK3CA p.Glu542Lys, which were detected from both his plasma and SLN-FNA samples.…”
Section: F I G U R Ementioning
confidence: 98%